2020
DOI: 10.9734/jsrr/2020/v26i230228
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Assessment of Nutritional Functional and Sensory Attributes of Complementary Foods from Maize-Carrot-Pigeon Pea Flour Blends

Abstract: Nutritive, less bulk and low cost complementary flour blends were produced from maize, carrot and pigeon pea. Five different blends of flour were formulated from maize, carrot and pigeon pea in the ratio of 100:0:0 (A), 90:5:5 (B), 85:5:10 (C), 80:5:15 (D) and 75:5:20 (E) while commercial formula (sample F) served as control. The formulated complementary flour blends were analyzed for their functional properties, proximate, selected mineral and vitamin compositions while the reconstituted samples (gruel) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The results obtained suggest that wheat-tigernut flour blends would be useful in food systems such as bakery products. The OAC was in line with Bello et al (2020) who reported OAC of 1.25-1.9 g/g for different ratios of complementary foods from maize, carrot and pigeon pea. WAC and OAC indicates enhanced hydrophobic character of proteins in flour (Kalar et al, 2022).…”
Section: Physicochemical Properties Of Wheat-tigernut Flour Blendssupporting
confidence: 90%
“…The results obtained suggest that wheat-tigernut flour blends would be useful in food systems such as bakery products. The OAC was in line with Bello et al (2020) who reported OAC of 1.25-1.9 g/g for different ratios of complementary foods from maize, carrot and pigeon pea. WAC and OAC indicates enhanced hydrophobic character of proteins in flour (Kalar et al, 2022).…”
Section: Physicochemical Properties Of Wheat-tigernut Flour Blendssupporting
confidence: 90%